Pengaruh Sertifikasi Halal Terhadap Pendapatan Pedagang Kaki Lima (Studi Kasus Bazar Kuliner Bazis Matraman Jakarta Pusat) - Jalaludin Jalaludin; Moch. Cahyo Sucipto; Ajeng Nurfajriyah (Jurnal Pelita Nusa, 2023)
This study aims to determine the effect of halal certification on the income of street vendors at the Bazis Matraman Culinary Bazaar and to determine how much influence halal certification has on the income of street vendors at the Bazis Matraman Culinary Bazaar. The method used in this research is descriptive quantitative with primary data sources in the form of observation results, questionnaires and interviews with the head of the traders and street vendors at the Bazis Matraman Culinary Bazaar, while secondary data is in the form of archives, journals, and news related to halal certification variables (X) and trader income (Y). The number of samples in the study was determined using the census technique with the results of 33 respondents. The results of this study can be concluded that based on the results of partial hypothesis testing using SPSS 29 for windows, the t test (partial test) results in a tcount value (-1.246) ≤ ttable (1.696) and a significance level of 0.222 ≥ 0.05, and the resulting coefficient of determination (R Square) test result of 0. 048, this shows that halal certification has a negative and insignificant effect on the income of street vendors at the Bazis Matraman Culinary Bazaar, while the level of influence produced is only 4.8%, while the remaining 95.2% is influenced by other variables not examined in the current study.